The formation and extinction of fear memory in tree shrews - Shang, Shujiang; Wang, Cong; Guo, Chengbin; Huang, Xu; Wang, Liecheng; Zhang, Chen (Frontiers in Behavioral Neuroscience, 2015)
Fear is an emotion that is well-studied due to its importance for animal survival. Experimental animals, such as rats and mice, have been widely used to model fear. However, higher animals such as nonhuman primates have rarely been used to study fear due to ethical issues and high costs. Tree shrews are small mammals that are closely related to primates; they have been used to model human-related psychosocial conditions such as stress and alcohol tolerance. Here, we describe an experimental paradigm to study the formation and extinction of fear memory in tree shrews. We designed an experimental apparatus of a light/dark box with a voltage foot shock. We found that tree shrews preferred staying in the dark box in the daytime without stimulation and showed avoidance to voltage shocks applied to the footplate in a voltage-dependent manner. Foot shocks applied to the dark box for 5 days (10 min per day) effectively reversed the light–dark preference of the tree shrews, and this memory lasted for more than 50 days without any sign of memory decay (extinction) in the absence of further stimulation. However, this fear memory was reversed with 4 days of reverse training by applying the same stimulus to the light box. When reducing the stimulus intensity during the training period, a memory extinction and subsequently reinstatement effects were observed. Thus, our results describe an efficient method of monitoring fear memory formation and extinction in tree shrews.